Serum 8-Oxo-dG as a Predictor of Sensitivity and Outcome of Radiotherapy and Chemotherapy of Upper Gastrointestinal Tumours. (23rd May 2018) - Pour Khavari, Ali; Liu, Yongping; He, Ellen; Skog, Sven; Haghdoost, Siamak
Abstract : The level of oxidative stress is important in the initiation and progression of various age-related diseases, such as cancer. The level of oxidative stress may also play a significant role in cancer patients' response to treatment. We aimed to investigate whether serum 8-oxo-dG as a marker of oxidative stress is a predictor of tumour response. We used modified ELISA with a two-step filtration to analyse 8-oxo-dG in serum. The relationship between 8-oxo-dG levels, tumour response, and toxicity was studied in 19 oesophageal cancer patients who received radiotherapy and 16 gastric cancer patients who received chemotherapy. In the radiotherapy and the merged radio- and chemotherapy groups, the baseline levels of 8-oxo-dG were significantly lower in responder patients than in nonresponder patients and the increments after treatment were greater. In comparison with patients whose serum 8-oxo-dG levels decrease after treatment, patients with increasing levels had a longer median "progression-free survival." Our results, although preliminary, suggest that serum levels of 8-oxo-dG may potentially be used to predict the sensitivity and outcome of radiotherapy and chemotherapy of upper gastrointestinal tumours. Patients with 8-oxo-dG levels that are low prior to treatment and subsequently increase after treatment may be more likely to benefit from the therapy.